In a Time of Crisis: Reflections on the Fortieth Anniversary of the Journal of Law and Religion - Dane, Perry (Journal of law and religion, 2025)
The Journal of Law and Religion began publishing as part of the larger revival and reimagination of the academic encounter with religion. More specifically, it sought from the start to examine an entire panoply of issues: secular law regarding religion, religious views of secular law and the state, political philosophy, political theology, religious law, and legal and religious pluralism as overarching ideas. What was at stake to the journal's founders was not just intellectual curiosity but their conviction that this kaleidoscope of concerns was essential to reconstituting a healthy polity, to play a role in responding to a crisis of values that afflicted both religion and the secular state. The journal has also sought to consider questions across the full range of world religions, including non-Western religions. Again, this is not expanding the canon for its own sake. The larger story of legal systems and religions in all their specificity and complex interactions, as revealed by rigorous and imaginative analysis, could ideally help establish a counter-narrative to the simple pieties of modernity. The challenges today, especially our current state of political polarization, which envelops religion in its wake, are different, but they demand the same careful, expansive, scholarly agenda.